IL6-receptor antibody tocilizumab as salvage therapy in severe chronic graft-versus-host disease after allogeneic hematopoietic stem cell transplantation: a retrospective analysis - Kattner, Anna-Sophia; Holler, Ernst; Holler, Barbara; Klobuch, Sebastian; Weber, Daniela; Martinovic, Danilo; Edinger, Matthias; Herr, Wolfgang; Wolff, Daniel (Annals of Hematology, 2020)
Chronic graft-versus-host disease (cGvHD) remains the most relevant factor affecting survival after allogeneic hematopoietic stem cell transplantation (alloHSCT). Besides corticosteroids (and ibrutinib in the USA), there is no established therapy for cGvHD. Tocilizumab, a humanized IgG1 IL6-receptor antibody, has shown efficacy in acute GvHD and cGvHD. We retrospectively analyzed the efficacy and safety of tocilizumab for the treatment of advanced cGvHD. Eleven patients with severe steroid refractory cGvHD (median age 49; range 21–62 years) that received at least two prior lines of therapy for cGvHD (range 2–8 regimens) were treated with tocilizumab (q4w, dosage 8 mg/kg IV) with a median number of 15 cycles (range 2–31). NIH consensus criteria grading for cGvHD were recorded prior to tocilizumab administration and after 3, 6, and 12 months of therapy. All patients received additional concomitant immunosuppression (IS) but no new IS within the last 4 weeks before start of tocilizumab and response assessment was terminated before start of any new IS. The median number of days between alloHSCT and initiation of tocilizumab therapy was 1033 days. Organs involved at initiation of tocilizumab therapy were skin (100%, all grade 3), eyes (82%), fascia (82%), mouth (64%), lungs (55%), and genitals (18%). Overall, 7/10 patients (70%) showed partial remission, 2/10 patients (20%) showed progressive cGvHD, 1/10 patient (10%) showed mixed response, and 1 patient died due to sepsis before first response assessment 1.5 months after initiation of treatment. Four patients required subsequent new immunosuppressive treatment. Two patients developed bacterial sepsis, one of whom died. The overall survival and relapse-free survival were 82% with an average follow-up of 22 months (range 1.5–52 months). Tocilizumab seems a promising treatment option in advanced cGvHD but further evaluation within a phase II trial is required.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Allogeneic hematopoietic stem cell transplantation; Chronic graft-versus-host disease; Interleukin-6; Tocilizumab